POLA KOMUNIKASI ORGANISASI DALAM PENINGKATAN KINERJA PEGAWAI DI KANTOR LURAH GUNG LETO KECAMATAN KABANJAHE - Deshinta Affriani Br Brahmana; Elisabeth Sitepu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
The purpose of the research is to find out how the influence of Organizational Communication Patterns in improving employee performance in The Office of Lurah Gung Leto Kabanjahe Sub-District improves employee performance. The data used in this study is primary data collected from the field through observation and in-depth interviews. The research method used is a qualitative approach. The informants in this study are as many as 10 people. As for the concept of the theory used by this study Miles and Huberman theory. Conclusion in the study, that the pattern of organizational communication in improving employee performance in the office of Lurah Gung Leto Kabanjahe sub-district uses a wheel communication pattern where the leader is in a central and influential position in the process of delivering messages and all running information must first be conveyed to the leadership and all reports, instructions, work orders and monitoring are centered on one person who leads but sees performance from the employee , where employees are still found arriving late and still found employees who do not carry out their basic duties and functions cause the pattern of wheel communication in Gung Leto Village Kabanjahe sub-district does not run well because the leadership in carrying out its main duties and functions less involve subordinates in achieving the organization's goals.